The risk of believing that emotions are bad and uncontrollable: association with orthorexia nervosa - L. Vuillier; M. Greville-Harris; R. L. Moseley (Eating and Weight Disorders)
Abstract Purpose This study aimed to explore emotional functioning in individuals with varying levels of orthorexia nervosa (ON) symptoms. Given the established links between emotion dysregulation and other eating disorders (EDs), and the conceptualization of ON within the ED spectrum, this research sought to examine the relationships between ON symptomatology and emotion regulation strategies, alexithymia, and beliefs about emotions. Methods A large sample (N = 562) completed self-report measures with high psychometric properties, assessing ON traits (E-DOS), emotion regulation strategies (DERS-SF and ERQ), alexithymia (TAS-20), and beliefs about emotions (ERQ). The study used well-validated measures to address limitations of previous research. Results Individuals with high ON traits demonstrated difficulties in most aspects of emotional functioning compared to those with low ON traits. Suppression, but not reappraisal, partially mediated the relationship between beliefs about emotions and ON symptoms. Believing emotions are bad or useless, difficulty controlling impulses, and relying on suppression to regulate emotions were most strongly associated with ON symptoms. Conclusion This study provides evidence that emotion dysregulation plays an important role in ON symptomatology. The findings suggest that when emotions feel unhelpful or uncontrollable, and maladaptive strategies like suppression are employed, individuals may seek perceived control through pathologically 'healthy' eating. There is currently no diagnosis criteria for ON, and consequently no clear treatment pathway. Our research suggests that specific aspects of emotional functioning such as beliefs about the usefulness of emotions or difficulties with feeling out of control when upset may be a useful treatment target to help individuals with ON develop healthier coping mechanisms and reduce reliance on rigid dietary rules as a means of emotional regulation. Level of evidence. Level III: Evidence obtained from well-designed cohort or case–control analytic studies.